Design and Numerical Simulation of Symmetric Multistage Canned Motor Pump - Xia, Bin; Kong, Fan-Yu (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Due to the advantages of high head, no leakage, multistage canned motor pump is widely used in the national economic construction department. At present, in the premise of guarantee reliability, saving energy efficient become an important development direction of canned motor pump. In order to research and improve the performance of the pump, this paper designed and used symmetric multistage canned motor pump DBP15-50x8 as the research object. Three-dimensional model of the main flow passage components is built and the mesh is generated respectively by using Pro/E and ICEM software, and we calculated the whole internal flow field of the pump that was selected by using ANSYS CFX software, achieving the pressure and velocity distribution rule in the pump and the internal details of flow in impeller and other main flow components. It is found that there is pre-whirl flow in the front of inlet in the first stage impeller under the conditions of 0.5 Q and Q flux, obtained the unstableness in inlet when this pump works under the low flux conditions. The post-processing showed the internal flow of bearing section and volute is chaotic, etc. The results provide theoretical basis for the design optimization of multistage canned motor pump.